Critical Regionalism and the Policies of Place: Revisiting Localism for the Digital Age. Issue 2 (20th November 2015) - Ali, Christopher
Abstract : Local broadcasting is at a crossroads in Western media systems. While regulators work to address emergent challenges, an enduring tension within the discourse of local media regulation remains how to define "the local." Stemming from the inability to meet this challenge, an artificial duality has emerged between communities of place and communities of interest within regulatory discussions. The larger epistemological question, therefore, remains undertheorized: How can we think through these issues in a productive fashion, rather than reducing them to an artificial dichotomy of spatial versus social? Through the use of illustrative instances from the United States, United Kingdom, and Canada, I argue that the neo‐Marxian theory of critical regionalism is a useful framework to approach this question.